Movimentos sociais e pós-colonialismo na América Latina - Ilse Scherer-Warren (Ciências Sociais Unisinos)
Considering the tradition of social movement studies in Latin America, the present text brings some refl ections about the emergence of a post-colonial approach directed to the study of subaltern groups on our continent. To fulfi ll this objective, the connections among four elements in the production of knowledge about contemporary social movements are examined: the relation between the subject studied and the subject that produces knowledge; the relation between life experience, representation and recognition; the human rights in the perspective of subaltern subjects; and discourse formations derived from the historicity and emancipatory desire of these subjects.